Endoparasitic helminth infection in Hemidactylus flaviviridis (Ruppel, 1835) (University Journal of Zoology, Rajshahi University, 2007)
Key words: helminth; house lizard; prevalence; intensity; hemidactylus flaviviridis Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 17-19